2010
DOI: 10.1029/2009jb006694
|View full text |Cite
|
Sign up to set email alerts
|

Low water content of the Cenozoic lithospheric mantle beneath the eastern part of the North China Craton

Abstract: [1] Nominally anhydrous minerals in 46 peridotite xenoliths hosted by Cenozoic basalts from five localities (Fangshan, Penglai, Qixia, Changle, and Hebi) of the eastern part of the North China Craton (NCC) have been investigated by Fourier transform infrared spectrometry (FTIR). The water contents (H 2 O wt %) of clinopyroxene (cpx), orthopyroxene (opx), and olivine (ol) range from 27 to 223 ppm, 8 to 94 ppm, and ∼0 ppm, respectively. On the basis of (1) the homogenous H 2 O content within single pyroxene grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
127
1
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(150 citation statements)
references
References 121 publications
(254 reference statements)
17
127
1
5
Order By: Relevance
“…6), consistent with a derivation from magmas (Simkin and Smith 1970;Garcia et al 1995;Ren et al 2004). Besides, Fo values in olivines in Xindian basalts are relatively low (Fo \ 85), compared with those of mantle xenoliths from Fan and Hooper 1989;Zheng et al 1998Zheng et al , 2001Zheng et al , 2006Fan et al 2000;Rudnick et al 2004;Xu and Bodinier 2004;Yang et al 2008;Chu et al 2009;Xia et al 2010;Xiao et al 2010). Furthermore, melt inclusions hosted by Xindian olivines are mostly isolated and thus original, in contrast with the absence of original melt inclusions in olivine xenocrysts (Schiano 2003).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…6), consistent with a derivation from magmas (Simkin and Smith 1970;Garcia et al 1995;Ren et al 2004). Besides, Fo values in olivines in Xindian basalts are relatively low (Fo \ 85), compared with those of mantle xenoliths from Fan and Hooper 1989;Zheng et al 1998Zheng et al , 2001Zheng et al , 2006Fan et al 2000;Rudnick et al 2004;Xu and Bodinier 2004;Yang et al 2008;Chu et al 2009;Xia et al 2010;Xiao et al 2010). Furthermore, melt inclusions hosted by Xindian olivines are mostly isolated and thus original, in contrast with the absence of original melt inclusions in olivine xenocrysts (Schiano 2003).…”
Section: Discussionmentioning
confidence: 74%
“…Melt fraction is displayed as percent along the melting curves H 2 O content in the source of Xindian basalts Previous studies on peridotite xenoliths in the NCC showed that H 2 O contents of these peridotites were generally lower than those of peridotites in other Archaean cratons, and Proterozoic or younger-age off-cratons, and abyssal peridotites Xia et al 2010). This suggests that the Cenozoic lithospheric mantle beneath NCC was rather dry Xia et al 2010).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations